Agroforestry research in India - SOLANKI, K R (The Indian Journal of Agricultural Sciences, 2013)
Agroforestry practice in India is old and traditional. Some systems have been researched since the late 19th centuryand there has been research on fodder-fuel plantations since the 1950's. Different agroforestry practices in India underdifferent agro-ecological regions arc described here with research results. It is concluded that there are several areas ofresearch on agroforestry)' yet to be untouched. Some of the systems are well described. There is need of greater researchon practice. The agroforestry research endeavour so far, apart from indicating possibilities for increased production offoodgrain, fodder and fuel, the system still needs greater research and management. The challenges and opportunitiesfor improvement are vast.